Proteins eluted from natural rubber crumb - Kekwick, Roy G. O. (2018)
The protein eluted from vulcanised natural and styrene butadiene rubber crumb samples has been subjected to total amino acid analysis and the total protein estimated. An antiserum raised to the NR crumb eluate reacted with the homologous immunogen and with polypeptides of the C-serum of fresh Hevea latex. The allergenicity of the natural crumb eluate has been compared to that ofhevein in skin prick testing.